(untitled) (Baghdad Science Journal, 2019)
It has been shown in ionospheric research that calculation of the total electron content (TEC) is an important factor in global navigation system. In this study, TEC calculation was performed over Baghdad city, Iraq, using a combination of two numerical methods called composite Simpson and composite Trapezoidal methods. TEC was calculated using the line integral of the electron density derived from the International reference ionosphere IRI2012 and NeQuick2 models from 70 to 2000 km above the earth surface. The hour of the day and the day number of the year, R12, were chosen as inputs for the calculation techniques to take into account latitudinal, diurnal and seasonal variation of TEC. The results of latitudinal variation of TEC show anomally called equatorial ionization anomally which presents two crests about the geomagnetic equators. The mean absolute percent errors MAPE for two numerical methods using the electron density profiles shown above were 0.0253, 0.02273 and 0.0213, 0.0124 respectively. The results of seasonal variation of TEC show a larger values for spring and autumn equinoxes other than for summer and winter seasons. The MAPE for autumn equinox has the smallest value than for summer, winter seasons and spring equinox. The MAPE for spring equinox equals to 0.01093 and 0.01015 for Simpson and Trapezoidal methods respectively. For autumn, summer and winter, the MAPE equals to 0.005825 and 0.006629 and 0.04682 and 0.0454, 0.01253 and 0.01231 for Simpson and Trapezoidal methods respectively.